The Growth And Production Of Brassica juncea L. Using Liquid Organic Fertilizer (LOF) Of Banana Tuber In Ultisol Land - Nardo Pardede; Akhmad Rizali; Noorkomala Sari (University of Prof. Dr. Hazairin, SH, 2022)
The productivity of mustard plants (Brassica juncea L.) in South Kalimantan in 2012 was 2.88 t ha-1, in 2013 it was 2.79 t ha-1, and in 2014 it was 2.68 t ha-1 which showed a decrease in mustard production in each year. Soil at South Kalimantan itself is contained the ultisol soil which has insufficient or less fertile nutrient content. These problems need to be addressed by adding organic matter. Banana weevil has local microorganisms and contains microorganisms that decompose organic matter that can improve soil nutrients. The banana hump contains 2.2 C/N, 0.09 ppm Fe, and 800 ppm Mg. These chemical elements are very influential on the vegetative growth of plants, especially the formation of leaves. This research was conducted to determine the best concentration of liquid organic fertilizer (LOF) on banana weeds on growth and yield of mustard plants. This study consists of 20 experimental units which used a one-factor completely randomized design with five treatments and four replications. Parameters observed in this study were plant height, leaf width, number of leaves, and wet weight of mustard plants. Based on the results of statistical research, this study showed that banana weevil LOF had a significant effect every week after planting on plant height, leaf width, number of leaves, and wet weight of plants. In the wet weight, LOF with a concentration of 200 mL + 800 mL water was able to increase the wet weight by 21.70 g compared to without LOF applied.